DINAMIKA RANTING NU 1 SIDOREJO DALAM PENERAPAN EKONOMI SYARIAH - Irfan Afandi (International Conference on Humanity Education and Society (ICHES), 2025)
This study examines the implementation of community-based Islamic economics through the initiative of Ranting Ekonomi Syariah (REKSYA), conducted by Ranting NU 1 Sidorejo in Banyuwangi. Within the context of the Society 5.0 era—marked by challenges such as climate change and economic inequality—Islamic economics, grounded in Islamic values, is viewed as a potential solution for building a just, sustainable, and spiritually oriented economic system. The research is motivated by low levels of Islamic financial literacy in rural areas, limited understanding of Islamic mu’amalah principles, and the dominance of conventional interest-based financial systems. Employing a site study approach, data were collected through observation and in-depth interviews with administrators and residents of Ranting NU 1 Sidorejo. The findings reveal that REKSYA NU has successfully developed a socio-economic ecosystem based on Islamic Social Finance principles, including interest-free microenterprise financing, free healthcare for the underprivileged (dhu’afaa), and scholarships for orphans and low-income families. These programs not only strengthen the social function of religious organizations but also promote economic self-reliance among villagers. The concept of the halal value chain is integrated into empowerment processes by optimizing local potentials such as agriculture and livestock. The success of REKSYA is evidenced by its recognition as a model “Kampung NU” at the regency level and active community participation in Islamic financial activities. The study concludes that religious organizations like NU play a vital role in fostering economic awareness and promoting Islamic financial inclusion at the grassroots level. It recommends the replication of similar models in other communities, with contextual adaptation and strong institutional support.